Estimated Greenhouse Gas Emissions from The Composting Process of Organic Waste in Karawang’s Urban Forest - Hurrul'Ain Quinizza; Wilma Nurrul Adzillah; Gina Lova Sari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The accumulation of organic waste in the form of leaves and branches that is not optimally managed in Karawang Regency has the potential to increase GHG emissions through the natural decomposition process. This study aims to estimate the amount of organic waste and GHG emissions generated from the management of leaves and twigs in the Karawang Urban Forest. The study was conducted using quantitative and qualitative approaches with purposive sampling of organic waste over eight days of observation, representing active waste management activities at the study site. GHG emissions were estimated using the 2006 IPCC Tier-1 guidelines due to limited local specific data, covering the waste sector (composting) and the energy sector (use of machinery and transportation). The results showed that the composting process produced relatively low GHG emissions compared to supporting activities, while the transportation sector was the largest contributor to emissions in the organic waste management system. These findings indicate that GHG emission mitigation strategies in organic waste management in urban areas need to focus on improving transportation and operational efficiency, accompanied by strengthening controlled aerobic composting practices to support more sustainable environmental management.